2008
DOI: 10.1089/jir.2006.0130
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive Expression of IL-18 and IL-18R in Differentiated IEC-6 Cells: Effect of TNF-αand IFN-γTreatment

Abstract: The multifunctional cytokine interleukin-18 (IL-18) is an important mediator in intestinal inflammatory processes. The aim of this study was to evaluate the constitutive expression of IL-18 and its receptors (IL-18R␣ and IL-18R␤) in intestinal epithelial cells (IEC) stimulated by tumor necrosis factor-␣ (TNF-␣) and interferon-␥ (IFN-␥). In addition, cellular proliferation and evaluation of brush border enzymes as differentiation markers were studied. Nontransformed rat intestinal epithelial IEC-6 cells were gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 55 publications
2
27
1
Order By: Relevance
“…In parallel studies, we measured Na ϩ -coupled butyrate uptake and SMCT1 mRNA levels in IEC-6 cells in response to TNF-␣ treatments. Earlier studies have shown TNF-␣ effects on IEC-6 cells, indicating expression of TNF-␣ receptors in this cell line (4,23). Our results showed that TNF-␣ inhibited Na ϩ -coupled butyrate uptake in a dose-dependent manner (Fig.…”
Section: Tnf-␣ Inhibits Smct1 Function and Expression In Iec-6 Cellssupporting
confidence: 73%
“…In parallel studies, we measured Na ϩ -coupled butyrate uptake and SMCT1 mRNA levels in IEC-6 cells in response to TNF-␣ treatments. Earlier studies have shown TNF-␣ effects on IEC-6 cells, indicating expression of TNF-␣ receptors in this cell line (4,23). Our results showed that TNF-␣ inhibited Na ϩ -coupled butyrate uptake in a dose-dependent manner (Fig.…”
Section: Tnf-␣ Inhibits Smct1 Function and Expression In Iec-6 Cellssupporting
confidence: 73%
“…In BALB/c and C57BL/6 mice DSS-induced colitis induces increased expression of IL-18 in the colonic mucosa, where it polarizes CD4 + T cells toward T helper cell type 1 (Th1)-mediated immune response [35] and thus increased production of the proinflammatory cytokine interferon (IFN)-g. IFN-g stimulated secretion of IL-18 from enterocyte-like IEC-6 cells has been correlated with IFN-g-increased expression of caspase-1 activity [36], an enzyme required for cleavage of the precursor form of IL-18 into mature biologically active IL-18. Indeed, inhibition of caspase-1 by the specific inhibitor pralnacasan [26] attenuated DSS-induced colitis, this effect being mediated by suppression of proinflamatory IL-18 and IFN-g.…”
Section: Discussionmentioning
confidence: 99%
“…Although activation of certain innate immune signaling receptors enhances IL-18 transcription in myeloid cells, IL-18 is generally considered to be constitutively expressed and stored as intracellular proIL-18 protein in most other cells (Kolinska et al, 2008;Nakanishi et al, 2001). Pro-inflammatory signals, through the activation of inflammasomes and caspases, trigger the proteolytical processing of proIL-18 to its active form, which is subsequently secreted by cells through a non-classical secretion pathway (Dinarello, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Although it does not play a dominant protective role in the lowdose model (Cai et al, 2000), IL-18 contributes to the development of small intestinal immunopathology after oral high-dose infection of T. gondii, partially through the induction of IFN-g production (Vossenkä mper et al, 2004). Previous studies suggest that Il18 mRNA as well as proIL-18 are constitutively produced by myeloid cells and intestinal epithelial cells (Kolinska et al, 2008). The generation of the active form of IL-18 requires inflammasome activation and caspase-mediated enzymatic cleavage (Gu et al, 1997).…”
Section: Introductionmentioning
confidence: 99%